Staying is nowhere : an anthology of Kondh and Paraja poetry - Mahapatra, Sitakant, 1937- (Writers Workshop ; agents in U.S., Inter Culture Associates, 1975)
Folk songs of the Kandh and Paraja peoples of Koraput and Phulbani districts, Orissa.